Americanization in Lithuania as a driving force for globalization - Agnė Šimelytė; Renata Korsakienė; Deniss Ščeulovs (Journal of Open Innovation: Technology, Market, and Complexity, 2017)
Purpose: The purpose of the article is to analyze Americanization patterns in Lithuania by exploring socio-economic and cultural factors and to determine the impact of Americanization on the level of globalization of the country and its economy. Design/ methodology: The research employs both qualitative and quantitative methods by using primary and secondary data. Further descriptive statistics, correlation regression, and factor analysis is applied. Carrying out the survey has collected primary data. Secondary data was drawn from the Statistics Lithuania, Premiercapital, and Swiss Federal Institute of Technology Zurich. Findings/ outcomes: The obtained and analyzed information on the spread of foreign capital, culture and their impact on social and cultural life in the host country which results in emigration and brain drain problems. On the other hand, the research allows us to examining the behavior of Lithuanians and their abilities to accept new culture and social life on the basis of own wealth. The results show that Americanization has much significant impact on economic growth rather than on globalization in Lithuania. Originality/ value: It is an interdisciplinary research, which covers three scientific areas: sociology, economics and mathematics. It is unique as it extends to the theory of globalization and synthesizes both understandings of Americanization: cultural assimilation and Americanization as the form of internationalization.
Keywords: F6; 650; Globalization; Americanization; McDonaldization; Lithuania